Adsorption of direct yellow brown D3G from aqueous solution using loaded modified low-cost lignite: Performance and mechanism. Issue 11 (12th May 2021) - He, Qiongqiong; Ruan, Pengfei; Miao, Zhenyong; Wan, Keji; Gao, Mingqiang; Li, Xinyuan; Huang, Shaomeng
ABSTRACT: Low-cost lignite-based, copper-containing adsorbents (Cu-raw) were developed through a simple ultrasonic impregnation protocol for enhanced adsorption of direct yellow brown D3G (DYB) from aqueous solutions while treating copper-containing wastewater. The adsorbent was characterized by X-ray diffraction (XRD), scanning electron microscopy-energy dispersion spectroscopy (SEM-EDS), Fourier transform infrared (FT-IR) spectroscopy and X-ray photoelectron spectroscopy (XPS). The adsorption isotherms and kinetics were studied, and the factors that affect the adsorption, such as adsorbent dosage and solution pH, were investigated. The results showed that DYB adsorption was highly pH dependent and the isotherm of adsorption could be well described by the Langmuir-Freundlich model and the maximum DYB adsorption capacity was estimated to be 369 mg/g at 25°C. The electrostatic and chelating interactions were the main interfacial interaction mechanism, and the synergetic removal performance of lignite toward cationic metal ions and anionic dye was shown. The kinetic data were well fitted to the pseudo-second-order equation, indicating that chemical sorption was the rate-limiting step. The findings reported in this work highlight the potential of using lignite as an effective low-cost adsorbent for the removal of organic pollutants from wastewater. GRAPHICAL ABSTRACT: